Tackling fallibility in women`s football - McCarron, J.; O'Malley, L.; Ong, C. W. (Sport Performance & Science Reports, 2020)
An uneasy paradox exists for performance scientists and clinicians in women's football: Performance science and medicine have contributed to its unprecedented success but are also potential limiting factors. This is due to our persistent failure to view women's football as a unique sport; in-stead, it is a version of football where performance at the highest level is achieved by men. The general tendency to prioritise knowledge creation and application in performance science and medicine with/for males, and then adapting themfor women only serves to confirm our biases